2013
DOI: 10.4081/jae.2013.408
|View full text |Cite
|
Sign up to set email alerts
|

Aerated lagooning of agro-industrial wastewater: depuration performance and energy requirements

Abstract: Intensive depuration plants have often shown low reliability and economic sustainability, when utilised for agro-industrial wastewater treatment, due to the particular wastewater properties: high organic load and essential oil concentrations, acidity, nutrient scarcity and qualitative-quantitative variability of effluents. Aerated lagooning systems represent a suitable alternative, because they are able to assure good reliability and low energy requirements, avoiding the drawbacks shown by the intensive depura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Andiloro et al [31] found low energy requirements (0.45 kWh kg COD −1 ) and a good treatment performance of full-scale aerobic-anaerobic aerated lagoons treating CPWW with high concentrations of essential oil (500-1000 mg L −1 ). Zema et al [25] simulated at laboratory scale the aerobic layer of aerated lagoons and indicated the possibility of decreasing the energy requirements (down to 0.16 kWh kg COD −1 ) through two measures: (i) reducing the aeration power (down to 0.6 W m −3 from the typical values of real-scale plants, about 2.5 W m −3 ); and (ii) limiting aeration time to the night (12 h only), when electricity cost is lower.…”
Section: Lagooningmentioning
confidence: 99%
“…Andiloro et al [31] found low energy requirements (0.45 kWh kg COD −1 ) and a good treatment performance of full-scale aerobic-anaerobic aerated lagoons treating CPWW with high concentrations of essential oil (500-1000 mg L −1 ). Zema et al [25] simulated at laboratory scale the aerobic layer of aerated lagoons and indicated the possibility of decreasing the energy requirements (down to 0.16 kWh kg COD −1 ) through two measures: (i) reducing the aeration power (down to 0.6 W m −3 from the typical values of real-scale plants, about 2.5 W m −3 ); and (ii) limiting aeration time to the night (12 h only), when electricity cost is lower.…”
Section: Lagooningmentioning
confidence: 99%
“…For these reasons, much attention has been recently paid to extensive systems for SW depuration, such as the aerobic and/or anaerobic lagooning plants (e.g., [14][15][16]). These extensive systems allow a proper equalisation of the physico-chemical characteristics of wastewater and a reduction of its pollutant load, as for other agro-industrial effluents [17][18][19]. However, the physico-chemical and biological processes of lagooning plants require a long time (weeks or even months), because the environmental conditions cannot be properly set up.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the depuration performance of the lagoon system, the decrease in the TSS concentration due to the lagoon process is well known [51]. The presence of a nonaerated tank promoted the activity of anaerobic bacteria, which degraded the organic matter concentration, and this also reduced the amount of the TSS [49,52,53]. Furthermore, the effect of aeration in the upstream tank promoted the flocculation process, due to the accelerated bacterial activity [52].…”
Section: Discussionmentioning
confidence: 99%
“…The aeration system was the same as the device described by [38,39,49], in which more details can be found. Downstream of the two tanks, a third smaller tank (which was not aerated) allowed SW storage before the subsequent treatment.…”
Section: Description Of the Experimental Systemmentioning
confidence: 99%